The Evaluation of Pre-service Preschool Teachers’ Knowledge about the Concept of Environment - Ahi̇, Berat; Ali̇si̇nanoglu, Fatma (Eurasian Society of Educational Research, 2015)
The purpose of the research is to evaluate pre-service preschool teachers' knowledge about environment by analyzing their drawings about it. 70 first grade, 99 second grade, 56 third grade and 44 fourth grade, with a total of 269 students have been evaluated in this research. This qualitative research was made with social structuralism vision. The data used in this research were gathered by draw and tell conversation technique, where pre-service teachers were asked to draw the first thing when they think about environment and explain it. When analyzing the data, both qualitative and quantitative techniques were used. After analyzing collected data, it is seen that most used object in drawings are tree, human, house and sun, respectively. 4 themes and 12 sub-categories under these themes are detected by pre-service teachers' drawings. The most drawn theme by pre-service teachers is Theme 3: a place which affected/designed by third persons, while the least drawn is Theme 4: a place where humans, animals and plants lives together. 10 categories have seen after analyzing explanations of the drawing. Most explanation seen in the places that supports human life category. Independent variables of the research (sex and grade level) and themes and explanations of the drawings are statically and meaningfully related to each other. The most significant result of this research is that pre-service preschool teachers have human-centric system of thought about environment.
Keywords: Eğitim Üzerine Çalışmalar; Studies on Education; Environment; preschool education; drawing; knowledge; pre-service preschool teacher; 13. Climate action; 4. Education; 7. Clean energy